Tradisi Dawuhan Sebagai Kearifan Lokal dalam Pelestarian Lingkungan Alam - Destina Marta Fiani; Yusrotin Meila Rizqina; Ainun Wahayuningtiyas; Noor Fatmawati (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2023)
Jrahi Village is one of the villages in Gunung Wungkal District, Pati Regency. This village is known as one of the villages that has a lot of local wisdom and nature conservation. One of them is that in Jrahi village there is a tradition that is still embedded in the lives of its people, namely the dawuhan tradition. This tradition is carried out after the rice planting season during the rainy season, namely in February. The place is at the foot of the mountain. The aim of this research is to provide an overview of the profile of Jrahi village as well as an overview of local wisdom in the form of the dawuhan tradition in Jrahi village which is a form of nature conservation in the village. The method used in this research is field research. Data collection in this research was carried out in three ways, namely interviews, observation and literature study. The results of this research show that the dawuhan tradition provides benefits for the village because this tradition aims to ensure that the water sources in this village continue to flow quite well when the rainy season arrives.